1992
DOI: 10.1002/ijc.2910520415
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical determination of androgen receptors in relation to oestrogen and progesterone receptors in female breast cancer

Abstract: The expression of oestrogen (ER), progesterone (PR) and androgen (AR) receptors in female breast cancer was investigated by immunohistochemistry on snap-frozen tissue specimens of a series of 100 breast cancers. For detection of the AR we used a recently developed mouse monoclonal antibody specific for the N-terminal domain of the human AR. Expression of AR was compared with that of ER and PR as well as with tumour grade and age. Of the breast cancers investigated, 76% were AR-positive. This high percentage co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
56
1
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(64 citation statements)
references
References 16 publications
6
56
1
1
Order By: Relevance
“…In limited studies over the last two decades, AR expression has been observed in 470% cases of breast carcinoma. [22][23][24] This figure is concordant with the AR expression in 80% of the cases in this study of 189 consecutive invasive breast cancers. Gonzalez et al 22 showed AR reactivity in 74.8% of 111 breast carcinomas using the same antibody clone and dilution used in this study.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…In limited studies over the last two decades, AR expression has been observed in 470% cases of breast carcinoma. [22][23][24] This figure is concordant with the AR expression in 80% of the cases in this study of 189 consecutive invasive breast cancers. Gonzalez et al 22 showed AR reactivity in 74.8% of 111 breast carcinomas using the same antibody clone and dilution used in this study.…”
Section: Discussionsupporting
confidence: 85%
“…In a series of 100 snap-frozen breast cancer tissues, Kuenen-Boumeester identified AR expression in 76% cases. 24 One large study of 488 cases from Poland has shown a lower rate (43.4%) of AR expression in breast carcinoma, but this study also reported much lower rates of ER (39.3%) and PR (24.6%) expression. 25 This study also used the same AR antibody clone and dilution as the a Four were luminal A and 4 were luminal B (see Table 2).…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…AR is expressed in approximately 35-75% of breast cancers. [8][9][10] Variations may be attributable to different methodologies and different fixatives, but a different case mix may also affect these studies. It has been shown that AR values correlate reasonably well with oestrogen receptor (ER) values, but more so with those for the progesterone receptor (PR).…”
mentioning
confidence: 99%
“…It has been shown that AR values correlate reasonably well with oestrogen receptor (ER) values, but more so with those for the progesterone receptor (PR). [8][9][10][11] AR positive breast cancer patients have prolonged survival and a better response to hormonal treatment than AR negative patients. Thus, some workers believe that knowledge of the receptor status of all three receptors may identify more accurately those patients with breast cancer who are most likely to respond to endocrine treatment.…”
mentioning
confidence: 99%